Pengaruh Penerapan Media Kartu Bilangan Berwarna Terhadap Hasil Belajar Matematika Materi Operasi Bilangan Bulat Siswa Kelas III UPTD SDN No.1 Budong-Budong, Kec. Budong-Budong, Kab. Mamuju Tengah - Hulyatul Auliya Arisma; Agustan Agustan; Muliati Samad (STIKes Ibnu Sina Ajibarang, 2023)
Based on the results of observations made on February 26, 2023 at SD Negeri 1 Budong-budong, the researchers obtained information through explanations from the teacher and homeroom teacher for class III at UPTD SDN No. 1 Budong-Budong, Kab. Central Mamuju where teachers have not used varied learning media which has resulted in less interest in learning mathematics so that it has an impact on students' quality and mastery of the material as well as having an impact on student learning outcomes themselves and showing less than optimal student learning outcomes in mathematics. The research objective in this study namely to find out the effect of the application of colored number card media on learning outcomes of mathematics on integer operations material for class III UPTD SDN No. 1 Budong-Budong, Kec. Budong-budong, Kab. Middle Mamuju. This research uses experimental research. Experimental research method. The sampling technique used is Saturated Sampling, which is a sampling technique when all members of the population are used as samples and the total population is relatively small, less than 30 people. The sample is class III with a total of 19 students. This study used descriptive analysis and inferential statistical analysis. Learning outcomes can be seen from the results of the posttest, which has an average score of 71.58, much different from the pretest result of 35.97. The results of this research hypothesis obtained that the sample selected in this study was class III with a total of 19 students. The results of the research hypothesis obtained tcount > ttable, namely 6.350 > 2.10092 and a sig value of 0.000 <0.05, so it can be concluded that H0 is rejected and H1 is accepted. integers for class III UPTD SDN No. 1 Budong-Budong, Kab. Central Mamuju.